Familial risk of systemic sclerosis and co-aggregation of autoimmune diseases in affected families. Issue 1 (December 2016) - Kuo, Chang-Fu; Luo, Shue-Fen; Yu, Kuang-Hui; See, Lai-Chu; Zhang, Weiya; Doherty, Michael
Abstract Background Systemic sclerosis (SSc) is a rare and devastating disease affecting skin and internal organs. Familial aggregation of SSc and co-aggregation with other autoimmune diseases is rarely reported. Methods We identified 23, 658, 577 beneficiaries registered with the National Health Insurance database in 2010, 1891 of whom had SSc. We identified 21, 009, 551 parent–child relationships and 17, 168, 340 full sibling pairs. The familial risks of SSc and other autoimmune diseases and familial transmission were estimated. Results The prevalence of SSc in the general population was 0.008 %. There are 3801 individuals had at least one first-degree relative with SSc, among them 3 people had SSc which was equivalent to a prevalence of 0.08 %. The adjusted relative risk (RR) (95 % CI) for SSc was 81.21 (11.40–579.72) for siblings of SSc patients. The familial transmission (genetic plus shared environmental contribution to total phenotypic variance of SSc) was 0.72. However, 84.1 % of patients were expected to be sporadic cases. The RR (95 % CI) in first-degree relatives of SSc patients was 2.64 (1.46–4.75) for rheumatoid arthritis, 6.51 (4.05–10.46) for systemic lupus erythematosus, 2.77 (1.04–7.35) for Sjögren's syndrome, 8.05 (2.03–31.92) for idiopathic inflammatory myositis, and 1.52 (1.15–2.01) for psoriasis. Conclusions The risks of SSc and other autoimmune diseases are increased in relatives of people with SSc, and family factors explain over two-thirds of the phenotypic variance of the disease. These findings may be useful in counselling families of patients with SSc and for further genetic studies.